2018
DOI: 10.1158/1078-0432.ccr-17-2967
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA–FEZF1-AS1 Promotes Tumor Proliferation and Metastasis in Colorectal Cancer by Regulating PKM2 Signaling

Abstract: Long non-coding RNAs (lncRNAs) play key roles in human cancers. Here, FEZF1-AS1, a highly overexpressed lncRNA in colorectal cancer, was identified by lncRNA microarrays. We aimed to explore the roles and possible molecular mechanisms of FEZF1-AS1 in colorectal cancer. LncRNA expression in colorectal cancer tissues was measured by lncRNA microarray and qRT-PCR. The functional roles of FEZF1-AS1 in colorectal cancer were demonstrated by a series of and experiments. RNA pull-down, RNA immunoprecipitation and luc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
221
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 246 publications
(229 citation statements)
references
References 39 publications
7
221
0
1
Order By: Relevance
“…Recent evidences have revealed that lncRNAs are frequently deregulated and play vital roles in many human cancers. Our previous studies revealed a variety of CRC related lncRNAs, which are involved in cancer promoting . In addition to these lncRNAs, we also discovered a potential oncogenic lncRNA, SNHG15, in CRC.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Recent evidences have revealed that lncRNAs are frequently deregulated and play vital roles in many human cancers. Our previous studies revealed a variety of CRC related lncRNAs, which are involved in cancer promoting . In addition to these lncRNAs, we also discovered a potential oncogenic lncRNA, SNHG15, in CRC.…”
Section: Discussionmentioning
confidence: 75%
“…Our previous studies revealed a variety of CRC related lncRNAs, which are involved in cancer promoting. [14][15][16][17] In addition to these lncRNAs, we also discovered a potential oncogenic lncRNA, SNHG15, in CRC. SNHG15 was initially found to be overexpressed in GC and could promote cell proliferation and invasion of GC.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…More research is needed to discover and develop effective biomarkers and targets for diagnosis and treatment of CRC. Recently, accumulating evidence has shown that long non-coding RNAs (lncRNAs), non-coding RNA transcripts longer than 200 nucleotides (4), are expressed differentially in various cancers including CRCs, suggesting that lncRNAs have roles in tumorigenesis and tumor metastasis (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence has shown the important roles of lncRNAs in cancers, especially their effects on cancer growth and malignant transformation. Dysregulation of some lncRNAs have been reported to regulate important cancer biological processes, such as proliferation (24), metabolism (25), metastasis (26) and cancer cells stemness (15). Recent evidence suggests that lncRNAs can act as ceRNAs to regulate miRNAs, subsequently to regulate expression of target genes.…”
Section: Discussionmentioning
confidence: 99%